2007
DOI: 10.1021/ic7007073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Substituents in the TpxCu Activation of Dioxygen:  An Experimental Study

Abstract: A series of TpxCu(I) complexes (Tpx=homoscorpionate ligand) have been reacted in solution with dioxygen at room temperature. Two different behaviors have been observed: the already described reaction with O2 or the lack of any transformation. The trend has been correlated with the electronic density at the metal center, and that has been evaluated by means of cyclic voltammometry studies as well as by IR studies with the TpxCu(CO) complexes. The data collected indicate that the former could serve as a better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…The most active catalysts were Cu(OTf) and Tp Br3 Cu(NCMe), in line with previous reports of being good catalysts for olefin aziridination reactions . Albeit both compounds displayed similar activities, we chose the complex Tp Br3 Cu(NCMe) to develop the scope of this system, in view of its remarkable stability in air, not only in the solid state but also in dichloromethane solution …”
Section: Methodssupporting
confidence: 64%
“…The most active catalysts were Cu(OTf) and Tp Br3 Cu(NCMe), in line with previous reports of being good catalysts for olefin aziridination reactions . Albeit both compounds displayed similar activities, we chose the complex Tp Br3 Cu(NCMe) to develop the scope of this system, in view of its remarkable stability in air, not only in the solid state but also in dichloromethane solution …”
Section: Methodssupporting
confidence: 64%
“…In a previous report from one of our laboratories we also found that a series of Tp x Cu complexes reacted with dioxygen and carbon dioxide in a consecutive sequence leading to dinuclear carbonato-bridged complexes. 24 Thus, we wondered about a possible implication of dinuclear intermediates in the aromatic hydroxylation reactions described in this contribution, in spite of being performed with hydrogen peroxide, and not with molecular oxygen. A series of catalytic experiments of benzene oxidation were run, varying the concentration of the catalyst [Tp *,Br Cu(NCMe)] from 0.0166 mM to 0.0666 mM.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the oxidation reaction of cyclohexane with H 2 O 2 was also reported with several Tp x Cu complexes (Scheme ), albeit in this case the overall reaction yield was maintained within the 10–22 % yield (cyclohexane‐based) despite the significant differences in electronic and steric properties of the Tp x ligand. Thus, Tp Br3 and Tp Me2 display similar steric hindrance around copper, but a large difference in the electronic effect onto the metal center (ca 51 cm –1 difference in the ν(CO) bands of their CO adducts) . Additionally, the bulkier Tp Ph does not show significant change in catalytic activity when compared with the parent Tp Me2 ‐containing catalyst.…”
Section: The Model Reactions and Their Selectivitiesmentioning
confidence: 96%